Selenium enriched vegetables as biofortification alternative for alleviating micronutrient malnutrition - El-Ramady, H. R.; Abdalla, N.; Fári, M.; Domokos-Szabolcsy, É. (International Journal of Horticultural Science, 2014)
There is a very difficult equation for malnutrition and over-consumption. That means malnutrition even of vitamins and/or minerals (Ca, Cu, Fe, I, Mg, Se and Zn, vitamin A) affects more than two billion people worldwide, largely due to low concentrations or poor bioavailability of the nutrients in the diet. In some developed countries in contrast, over-consumption, particularly of over-refined cerealbased foods, has contributed to the development of an epidemic of metabolic diseases. So, producing nutritious and safe foods sufficiently and sustainably is important target at the same time challenge of modern agriculture. In the past, great efforts have focused only on increasing crop yields, but enhancing the concentrations of mineral micronutrients has become an urgent task. The main daily food source is the staple crops specially in developing countries of the world, i.e., wheat, rice, cassava, beans, sweet potato or maize. These kind of plants are often deficient in some of mineral elements. Thus, the increasing of bioavailable concentration of micronutrients in edible crop tissues (via biofortification) has become a promising strategy in modern agriculture, providing more nutritious foods, to more people, with the use of fewer lands. Biofortification of these trace elements can be achieved application with agronomic process such as soil or foliar fertilization or crop breeding even conventional technic and/or genetic engineering. This review highlight progress to date and identify challenges faced in delivering biofortified vegetable crops as well as the agronomic approaches and tools to improve crop yield and micronutrient content of food crops.